Kepribadian Proaktif, Keterampilan Kerja, dan Kinerja Usaha pada Badan Usaha Milik Desa - Handayani, Juli; Indra Surya Permana; Reza Rahmadi Hasibuan (DFAME Digital Financial Accounting Management Economics Journal, 2024)
This study aims to examine the impact of proactive personality on business performance and assess the role of job crafting as a mediating factor in the connection between proactive personality and business performance. The research will utilize a quantitative methodology and encompass the entire population of 53 business from BUMDes in Sokaraja District as the research sample. The sampling approach use saturated samples when the whole population is utilized as a research sample. The data was analyzed using SmartPLS. The data analysis revealed the following findings: 1) Proactive personality has a positive effect on business performance, 2) Job crafting influences business performance, 3) Proactive personality has a positive effect on job crafting, and 4) Job crafting as a mediator between proactive personality and business performance. Implications that can be inferred from the conclusions above are that BUMDes parties are anticipated to adopt a more inclusive approach, rather than only employing a hierarchical structure in BUMDes management, to provide business with greater autonomy to engage in job crafting.